The effect of (Marzona) model in learning technical performance of some basic volleyball skills for female students - Hadi, Sarah Salah; Amir, Hamida Obaid Abdel (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research lies in designing an educational program according to the Marzona model and the extent of the impact of the model on learning the technical performance of some basic skills in volleyball for female students, and how this model helps in the manner of learning. The Marzona model depends on helping teachers to plan the educational curriculum better by using what they know of information about how students are taught. The mission of this model lies in helping students to become able to learn to think with the motor skill on their own and encourage them to self-research, and it is important Also in the call to teaching for the sake of thinking and not to remember and forget, so that learning for the learner is like breathing for life.